Agronomic Properties and Essential Oil Composition of Basil Varieties of Landraces (Ocimum basilicum L.) in Turkey - KACAR, OYA; GOKSU, ERDIN; AZKAN, NEDIME (Asian Journal of Chemistry, 2010)
The objective of this study was to determine some agronomic properties, essential oil ratio and composition of some varieties and different sources of Ocimum basilicum L. landraces in Turkey. During 2002- 2003, field trials were conducted at Uludag University, Faculty of Agriculture, Department of Field Crops, Bursa, in South Marmara region of Turkey. Four varieties and six landraces of Ocimum basilicum L. were included in the study. Field trials were arranged in the complete randomized block design with three replications. As a result of this research, it was determined that the highest values of plant height (46.3 cm), green herb yield (4386.4 kg ha-1), drug herb yield (867.8 kg ha-1), essential oil ratio (0.90 %) and essential oil yield (8.02 L ha-1) were obtained from V-1. In addition, V-2 (0.88 %) and LR-5 (0.87 %) should be taken into consideration in terms of essential oil ratio. Taking into consideration of the chemical composition, it could be stated that the ‘linalool’ chemotype was found 80 % (V-1, V-2, V-3, V-4, LR-1, LR-3, LR-4 and LR-6), ‘methyl eugenol/linalool’ chemotype was found 10 % (LR-2) and ‘methyl chavicol’ chemotype was found 10 % (LR-5) of the investigated Ocimum landraces and varieties.